Radiocarbon dates of burials from Ceibal and other Pasión Maya sites, Guatemala, and the examination of freshwater reservoir effect through diet reconstruction. (August 2022) - Inomata, Takeshi; Sharpe, Ashley; Palomo, Juan Manuel; Pinzón, Flory; Nasu, Hiroo; Triadan, Daniela; Culleton, Brendan J.; Kennett, Douglas J.
Highlights: Bayesian model effectively reconstructs the human diet based on stable isotope data. Freshwater reservoir offset of 596 ± 422 years was obtained from modern samples. Diet reconstruction and the offset allowed radiocarbon date correction. Preceramic burials may be contemporaneous with ceremonial construction. Abstract: In the Maya lowlands, where bedrock consists largely of carbonate rocks, aquatic organisms living in inland bodies of water may incorporate inorganic carbon derived from those rocks. Their tissues may reflect the freshwater reservoir effect (FRE), which would give radiocarbon dates older than those of contemporaneous terrestrial plants. FRE may also affect humans and terrestrial animals that consume those aquatic organisms. To evaluate the FRE of the Pasión River region of Guatemala, we radiocarbon dated modern fish and mollusks, as well as mollusk shells and terrestrial plants found in a lake core. The modern fish and the mollusk soft tissues indicated a radiocarbon age offset of 596 ± 422 years, whereas lake core samples gave an offset of 2124 ± 148 years. The difference most likely resulted from the incorporation of inorganic carbon in shell carbonate in addition to metabolic carbon. We applied these data to 50 radiocarbon dates of human remains excavated from Ceibal and nearby sites. To estimate the portion of aquatic organisms in their diet, we analyzed carbon and nitrogen stable isotopes of these remains with the Bayesian mixing model FRUITS (Food Reconstruction Using Isotopic Transferred Signals). The offset of 596 ± 422 years led to radiocarbon date corrections of 92–179 years to human remains from the Middle Preclassic period and 44–99 years to those from the later periods. The applications of FRE corrections suggest that groups maintaining an Archaic way of life may have coexisted with ceramic-using groups when ceremonial complexes were built. This study indicates the importance of considering FRE in chronology building, particularly for the Preclassic period.